MICROWAVE-HYDROTHERMAL HEXAMETHYLENETETRAMINE-MEDIATED SYNTHESIS OF NANOCRYSTALLINE MnO2 - O. M. Gaytko; A. E. Baranchikov; V. K. Ivanov (Тонкие химические технологии, 2018)
The article considers a non-conventional approach to the synthesis of various polymorphic modifications of manganese dioxide. The approach consists in hydrothermal microwave processing of a reaction mixture containing potassium permanganate and hexamethylenetetramine. We emphasize the relevance of the work due to such MnO2 properties as catalytic and photocatalytic activity, its application in accumulators, supercondensers and biochemistry. We report on the first detailed study on the role of temperature, synthesis duration and pH value on the phase composition and morphology of nanocrystalline MnO2. We show that the phase composition of manganese dioxide is largely determined not only by temperature, synthesis duration and pH value, but also by the acid added to the reaction mixture (nitric or sulphuric). In particular, the presence of sulfuric acid apparently results in α-MnO2 stabilization. It is noted that the type of the acid used in the course of the synthesis, as well as other synthesis conditions exercise no significant influence neither on the shape nor on the size of α-, γ- and δ-MnO2 particles. In contrast, the morphology of β-MnO2 turned out to be extremely sensitive to the synthesis conditions. Long (24 h) hydrothermal processing of reaction mixtures at рН 0.5-1 results in the formation of single-phase pyrolusite. The microstructure of the latter is determined by the reaction mixture composition.